GLOBAL TRENDS AND PROSPECTS IN EMPLOYEE WELL-BEING RESEARCH: A BIBLIOMETRIC ANALYSIS FROM 1950 TO 2022 - Nadira Mohd Rawi; Sharifah Khairol Musairah; Sabiroh Md Sabri (International Journal of Accounting, Finance and Business, 2022)
A sustainable workforce depends on the health of its workers. To maintain a viable workforce, each organization must be concerned for its employee well-being. Nevertheless, the issues regarding employee well-being remain and it has called for more research on this topic. This article includes a bibliometric analysis of employee well-being that has been examined using the VOSviewer1.6.18 to assess the worldwide research trends, including the growth of publications, popular themes, publishing outputs by nations, and co-occurrences of author keywords. Searches were done in the article title using the keyword â€œEmployee Well-beingâ€. This study retrieved 3,134 documents from the Scopus database. Data analysis tools used included data visualisation, citation metrics and frequency analysis. The results demonstrate a consistent increase in the number of research publications on employee well-being for the past 72 years since 1950. Researchers from the United States wrote the majority of the articles, followed by those from the United Kingdom, Australia, and Germany. India was the only Asian country listed among the top ten of the publication lists by country, which implies a scarcity of research on employee well-being by researchers from Asian countries. A closer look at the co-occurrences of author keywords revealed that the keyword â€œemployee wellbeingâ€ has the highest co-occurrences, which are 3568 links and the highest total link strengths, which are 2526 links. It can be concluded that future researchers could use the results from the analysis to explore research areas related to employee wellbeing.